MANAJEMEN APLIKASI MODEL HIDROLOGI ELEMENTER DALAM PENGENDALIAN EROSI DAN SEDIMEN DAERAH ALIRAN SUNGAI PROGO HULU - , Delima Lailan S Nst ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The high of rainfall distribution accompanied with land use condition that doesnât consider to the rules of conservation is the main factor to reduce the healthy of Upstream Progo Watershed. Therefore, watershed management is needed to increase watershed condition. The main aspects that always be considered in watershed management are hydrologic aspect (water yield, coefficient of river regim), erosion, and sedimentation. This research aims to asses performance of NRECAâs Model at Upstream Progo Watershed in predicting water yield, coefficient of river regim, runoff coefficient, and sedimentation. Furthermore, this research aims to asses performance of MUSLE Methods in predicting erosion. The accuracy test of NRECAâs Model and MUSLE Methods show that both models are approriate enough to be applied in Upstream Progo Watershed which characterized by satisfactory statistical and graphics test result. Predicted results of watershed health indicators (maximum discharge, minimum flow, coefficient of river regim, water yield, erosion and sedimentation) showed that Upstream Progo Watershed was in a bad condition. To increase the watershed condition, the optimization of watershed management is done by applying landuse changes simulation based on land cover index. Landuse changes simulation results showed significantly decrease of erosion and sedimentation on each scenarios.